IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Nurharfah Haron - Haron, Nurharfah (2015)
Article on: Article 1 - “The Use of Video as an Audio-Visual Material in Foreign Language Teaching Classroom” Article 2 – “Incorporating audio-visual materials in university teaching: Results of a faculty survey and corresponding actions of the Library”